The Linguistic Research of Nonverbal Component of a Composit Verbal / Visual Text: Problems of Verbalization Sense - E. L. Daylof (Теория и практика судебной экспертизы, 2016)
The article is devoted to the methodical issues in the point of the non-verbal component analysis within the framework of linguistic research of composit verbal/ visual texts relevant to extremism prevention. The examples of expert practice functions of nonverbal components of a composit verbal/ visual text, types of semantic bounds between the visual and verbal part in different types of composit verbal/ visual texts are discussed. The algorithm for semantic analysis of composit verbal/ visual texts as an object of forensic assessment is suggested.